An improved rovibrational linelist of formaldehyde, H212C16O. (May 2021) - Al-Derzi, Afaf R.; Tennyson, Jonathan; Yurchenko, Sergei N.; Melosso, Mattia; Jiang, Ningjing; Puzzarini, Cristina; Dore, Luca; Furtenbacher, Tibor; Tóbiás, Roland; Császár, Attila G.
Highlights: Comprehensive analysis of available rotation-vibration data High-accuracy measurements of pure rotational transitions within 4 states High accuracy line list presented. Graphical abstract: Abstract: Published high-resolution rotation-vibration transitions of H 2 12 C 16 O, the principal isotopologue of methanal, are analyzed using the MARVEL (Measured Active Rotation-Vibration Energy Levels) procedure. The literature results are augmented by new, high-accuracy measurements of pure rotational transitions within the ground, ν 3, ν 4, and ν 6 vibrational states. Of the 16 596 non-redundant transitions processed, which come from 43 sources including the present work, 16 403 could be validated, providing 5029 empirical energy levels of H 2 12 C 16 O with statistically well-defined uncertainties. All the empirical rotational-vibrational energy levels determined are used to improve the accuracy of ExoMol's AYTY line list for hot formaldehyde. The complete list of collated experimental transitions, the empirical energy levels determined, as well as the extended and improved line list are provided as Supplementary Material.